2017
DOI: 10.3389/frobt.2017.00046
|View full text |Cite
|
Sign up to set email alerts
|

A Modular, Reconfigurable Mold for a Soft Robotic Gripper Design Activity

Abstract: Soft robotics is an emerging field with strong potential to serve as an educational tool due to its advantages such as low costs and shallow learning curves. In this paper, we introduce a modular and reconfigurable mold for flexible design of pneumatic soft robotic grippers. By using simple assembly kits, students at all levels are able to design and construct soft robotic grippers that vary in function and performance. The process of constructing the modular mold enables students to understand how design choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Grippers using FEAs represent one of the most mature technologies among soft grippers, such that the technology has been already spun off in industrial companies, and also used for educational purpose . However, most of the existing grippers manipulate only centimeter‐size objects and have limited or more often simply no sensing.…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…Grippers using FEAs represent one of the most mature technologies among soft grippers, such that the technology has been already spun off in industrial companies, and also used for educational purpose . However, most of the existing grippers manipulate only centimeter‐size objects and have limited or more often simply no sensing.…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…The modular design can foster the confidence of students and meet education objectives to a certain extent due to its simple operation characteristics. 85 In summary, the molding method is a cost-efficient and facile process for the preparation of soft robots. However, it is difficult to manufacture internal volumes, undercuts, and complex internal structures, and the bubble-induced defects in the molding process need to be solved.…”
Section: Moldingmentioning
confidence: 99%
“…Using design‐based research, analysis in years one to three of our project has demonstrated feasibility and led to improvements to the soft robotics curriculum for classroom settings. The molds and initial instructional plans were refined through small‐scale, local implementation before being expanded to multi‐district training and implementation for the research evaluation (A. Jackson, Zhang, et al, 2017; Zhang et al, 2017). Teacher recommendations were integrated into the lesson plan, and the lesson has been well received by these participating teachers.…”
Section: Curriculum Contextmentioning
confidence: 99%